ANALISIS PENGGUNAAN ALIH KODE DAN CAMPUR KODE DALAM VIDEO BLOG CHANNEL YOUTUBE CHAKURIN FUUFU - Rama Tri Wulandari; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Code-switching and code-mixing are phenomena commonly observed in daily life, including in video blogs (vlogs) on YouTube channels. This study aims to explain the forms of code-switching and code-mixing present in the vlogs on the YouTube channel Chakurin Fuufu. This research uses a qualitative descriptive approach, with data in the form of utterances containing code-switching and code-mixing. The data sources are two video titles from the Chakurin Fuufu YouTube channel. The study concludes that the most frequent type of code-switching identified is inter-sentential switching, with 8 instances, followed by intra-sentential switching with 1 instance, and tag-switching, also with 1 instance. Regarding code-mixing, the most commonly found type is insertion with 14 instances, followed by alternation with 3 instances, and congruent lexicalization with 1 instance.